Normetanephrine and Glucose Acute Responses to Aerobic Boxing with Kinect Xbox with and without Blood Flow Restriction as a Strategy against Inactivity in Non-Athletes - Zeinab Sadat Mousavi; farshad ghazalian; Mandana Gholami; Hossein Abed Natanzi; Khosrow Ebrahim (Tehran University of Medical Sciences, 2021)
Background and Aim: Inactivity increases the risk of chronic diseases. The aim of the present study was to investigate the acute changes in Normetanephrine and glucose in boxing with Kinect Xbox with and without blood flow restriction as an alternative to aerobic exercise during quarantine in young non-athletes. Material and Methods: Fourteen healthy non-athlete individuals with a range of 20 to 40 years of age were randomly and purposefully selected. And on two different days with and without restriction of blood flow, they played boxing with Xbox 360 for 20 minutes. Blood samples were taken before and immediately after Results: There was a significant increase in serum Normetanephrine playing compared to before the test in both training groups, but the amount of changes between the two groups with and without blood flow restriction was not significant (P≤0.05). Exergames, in the case of unrestricted blood flow, has a significant effect on glucose, but the restriction of blood flow did not lead to a significant difference in the amount of glucose (P≤0.05). Conclusion: Exergames provide the necessary stimulus for catecholamine secretion and glucose response, and it is recommended for people with limited blood flow. Further studies are needed on the effect of restricting blood flow as a new training method on video game with movement.